Field Chemical Immobilization of Andean and Pampas Cats in the High‐Altitude Andes - Tellaeche, Cintia Gisele (2020)
Three protocols (Ketamine–Medetomidine, Ketamine–Xylazine and Ketamine–Medetomidine–Midazolam) were used to immobilize 2 sympatric wild cat species, the critically endangered Andean cat (Leopardus jacobita ), and the relatively more common Pampas cat (L. colocolo ), in the high Andes Mountains of Argentina between September 2011 and May 2016. Based on 8 Andean cat capture events and 9 Pampas cat capture events, we determined that the ketamine–medetomidine combination safely induced 45 minutes of anesthesia at a dosage range of ketamine: 6–9 mg/kg, medetomidine: 0.05–0.08 mg/kg for field immobilization. Heart rate, respiratory rate, and oxygen saturation remained within acceptable limits during all captures, but we had cases of hyperthermia in animals captured during the day. There was no evidence of a decline in the health condition of any animals recaptured 148–1,290 days post–initial capture.